Effective Management: A Catalyst for Organizational Performance - Ali Junaid Khan; Asifa Jahangir; Waseem Ul Hameed; Jawad Iqbal (iRASD Journal of Management)
The objective of this study was to identify the relationship between effective management and the organizational performance of small and medium enterprises (SMEs). It is a fact that in modern times, the performance of SMEs is critical to improving because these entities have a great contribution to the economy of Pakistan. The earlier studies have highlighted the management crisis in organizational performance. In this regard, the study is based on the cross-sectional data collection on the Likert scale questionnaire. The study highlights that there is a critical role for goal setting, a sense of ownership, and teamwork in effective management to improve the performance of SMEs. This study is significant because it provides both theoretical and practical implications that are important to consider when it comes to the performance of SMEs. The implications of this study would be useful for management to ensure effective practices to improve the performance of the organization.